PKM Education on Occupational Safety and Health in the COVID 19 Pandemic to Employees of PT. Astamukti Airtech Nusatama - Galuh Krisna Dewanti; Elfitria Wiratmani; Ridwan Usman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic has changed the order of society, it is recommended that they are even forced to stay at home, go to school, work and even worship at home. Almost all countries urge their citizens not to move outside the home if there is no urgent need. Informal workers because around 61 percent of the global workforce are particularly vulnerable during the pandemic, have to face higher OSH risks, and lack adequate protection. Occupational Health and Safety (K3) is a thought and effort to ensure the integrity and perfection of both the physical and spiritual workforce, in particular, the implementation of Community Service (PKM) in the Covid-19 pandemic to employees of PT. Astamukti Airtech Nusatama. The results of the socialization and education of K3 employees better understand and realize the importance of the OHS system and the implementation of the Covid-19 pandemic health protocol in the workplace, the importance of management support that continuously provides understanding through discussion and training so that they are aware, understand and be able to consistently apply K3 and health protocols continuously in the corporate environment.